Seasonal changes in gene expression of steroidogenic enzymes, androgen and estrogen receptors in frog testis. (30th July 2016) - Santillo, Alessandra; Falvo, Sara; Chieffi Baccari, Gabriella; Di Fiore, Maria Maddalena
Abstract: The anuran amphibian Pelophylax esculentus shows an annual cycle of sexual steroid production and spermatogenesis. To more thoroughly comprehend the steroidogenic pathways that govern the seasonal reproductive cycle, we investigated the mRNA expression of key enzymes involved in the androgenic and oestrogenic biosynthesis pathways in the testis of frogs taken in the reproductive and postreproductive period. Furthermore, we also analysed androgen and oestrogen levels and their own receptor gene expressions. Our findings showed that during the reproductive period, 3β‐hydroxysteroid dehydrogenase, 17β‐hydroxysteroid dehydrogenase and 5α‐reductase mRNA levels were higher than those during the postreproductive period. High testosterone and 5α‐dihydrotestosterone titres as well as the expression levels of androgen receptors in the reproductive testis strongly confirmed that the androgenic pathway is necessary for spermatogenesis activation. Conversely, during the postreproductive period, the highest P450 aromatase, estrogen receptor α and β mRNA levels, paralleling with oestradiol titres, indicated that the oestrogenic pathway is essential for the interruption of the reproductive processes. Our findings demonstrated, for the first time in amphibians, that testicular endocrine cyclic activity could be modulated by the up‐regulation of key steroidogenic enzyme gene expressions. This in turn determines the activation of the androgenic pathway in reproductive phase and the oestrogenic one in postreproductive phase.